2017
DOI: 10.1007/s10606-017-9275-z
|View full text |Cite
|
Sign up to set email alerts
|

Counter-Discourse Activism on Social Media: The Case of Challenging “Poverty Porn” Television

Abstract: In this paper we investigate how online counter-discourse is designed, deployed and orchestrated by activists to challenge dominant narratives around socio-political issues. We focus on activism related to the UK broadcast media's negative portrayal of welfare benefit claimants; portrayals characterised as "poverty porn" by critics. Using critical discourse analysis, we explore two activist campaigns countering the TV programme Benefits Street. Through content analysis of social media, associated traditional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Through analysis of the We Are Beneficiaries social media campaign, this paper contributes to addressing a gap in knowledge about the role of social media in the de‐stigmatisation of poverty. Social media for political activism has been acknowledged in the literature (Al‐Rawi ; Feltwell et al ; Velasquez and LaRose ), yet little has been said about social media for activism against poverty stigma. While stigmatisation can be perpetuated by social media (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through analysis of the We Are Beneficiaries social media campaign, this paper contributes to addressing a gap in knowledge about the role of social media in the de‐stigmatisation of poverty. Social media for political activism has been acknowledged in the literature (Al‐Rawi ; Feltwell et al ; Velasquez and LaRose ), yet little has been said about social media for activism against poverty stigma. While stigmatisation can be perpetuated by social media (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Rogers et al (), in a somewhat rare exception, found potential in digital media production to “talk back” to and transform policy and research practices that reproduced stigma, through their collaborative projects with social housing tenants (see also Arthurson et al ). In the age of digital communications, social media are key spaces in which news stories are distributed, political debates are engaged with and activism campaigns are mobilised (Feltwell et al ). While conglomeration is one key feature of media convergence identified by Cupples and Glynn (), this is countervailed by the fragmentation, contestation, and shifting power relations concomitant with digitalisation.…”
Section: Poverty (De)stigmatisation and (Social) Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…break out of what were likely to be relatively closed local university worker networks and reach other university workers across the UK, as well as a more general public). This (attempted) ‘gaming’ of Twitter’s trending algorithm is something that is also seen in other tools, such as Thunderclap.it – a ‘crowdspeaking’ service which temporally coordinates large-scale tweeting efforts to ‘increase [the] social reach’ (Wardle, 2014) of such things as online activist campaigning (see Feltwell et al [2017] for an example of the usage of Thunderclap.it in relation to anti-‘Poverty Porn’ activism). Given this was not an empirical study, no evaluation of @_Zen_Bot_’s success in this regard was attempted.…”
Section: My Unexpectedly Militant Botsmentioning
confidence: 97%
“…This proliferation of bots has also suggested a capacity for digital technologies to function as sites of political deliberation and ‘hacktivism’ (Jordan, 2002; Jordan & Taylor, 2004) – the disruption of social injustice via (‘homemade’/‘grassroots’) computational and technological innovations. As such, spaces like social media platforms are not just forums for talking about socially relevant issues (though that is part of what goes on there: see Brooker et al, 2015, 2018; Feltwell et al, 2017), but where digital automated tools can be, and routinely already are, leveraged to assist in that work. As such, bots demand sociological consideration.…”
mentioning
confidence: 99%